CONFIRMATION BIAS, SELF-ATTRIBUTION BIAS, DAN OVERCONFIDENCE DALAM TRANSAKSI SAHAM - Supramono Supramono; Marisa Wandita (Jurnal Keuangan dan Perbankan, 2017)
Overconfidence caused investors overestimate their knowledge, underestimate risk and exaggerate their ability to control events. This led to excessive trading, unwarranted risk taking, and ultimately, financial losses. The aim of this study was to analyze the relationship of overconfidence and confirmation bias and self-attribution bias. The subjects in this experiment were 53 students in finance classes at Faculty of Economic and Business.Data that had been collected was analyzed using descriptive and inferential analysis techniques using bivariate correlation. The result of this study showed that there was a positive relationship between confirmation bias and overconfidence. However, there was no a positive relationship between self-attribution bias and overconfidence.   Overconfidence menyebabkan investor melebih-lebihkan pengetahuan mereka, meremehkan risiko, dan membesar-besarkan kemampuan mereka untuk mengontrol suatu kejadian. Hal ini menyebabkan trading yang berlebihan, pengambilan risiko yang tidak beralasan, dan akhirnya, kerugian keuangan. Tujuan dari penelitian ini adalah untuk menganalisis hubungan confirmation bias, overconfidence, dan bias self-attribution. Subyek dalam penelitian ini adalah 53 mahasiswa di kelas keuangan di Fakultas Ekonomi dan Bisnis. Data yang telah dikumpulkan kemudian dianalisis menggunakan teknik analisis deskriptif dan inferensial menggunakan korelasi bivariat. Hasil penelitian ini menunjukkan bahwa ada hubungan positif antara confirmation bias dan overconfidence. Namun, tidak ada hubungan positif antara self-attribution bias dan overconfidence.